2009
DOI: 10.1038/ncb1965
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular fluid flow in rapidly moving cells

Abstract: Cytosolic fluid dynamics have been implicated in cell motility 1-5 because of the hydrodynamic forces they induce and because of their influence on transport of components of the actin machinery to the leading edge. To investigate the existence and the direction of fluid flow in rapidly moving cells, we introduced inert quantum dots into the lamellipodia of fish epithelial keratocytes and analysed their distribution and motion. Our results indicate that fluid flow is directed from the cell body towards the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
199
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(215 citation statements)
references
References 33 publications
15
199
1
Order By: Relevance
“…Myosin contraction can contribute to rear retraction as well as promote motility by enhancing actin disassembly (7) and inducing forward directed fluid flow (27). However, it is not required; knockouts and inhibition experiments have shown that although myosin II typically promotes movement and increases cell speed, it is not essential for motility in many cell types including keratocytes (5,7,27), Acanthamoeba (28), and Dictyostelium discoideum (29). Here we show that myosin II has a negligible role in rear retraction in keratocyte fragments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Myosin contraction can contribute to rear retraction as well as promote motility by enhancing actin disassembly (7) and inducing forward directed fluid flow (27). However, it is not required; knockouts and inhibition experiments have shown that although myosin II typically promotes movement and increases cell speed, it is not essential for motility in many cell types including keratocytes (5,7,27), Acanthamoeba (28), and Dictyostelium discoideum (29). Here we show that myosin II has a negligible role in rear retraction in keratocyte fragments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic streaming in the green algae Chara and Nitella has been proposed to have a role in mixing nutrients (4). In migrating cells, cytoplasmic streaming is considered to facilitate the transport of actin monomers in the direction of cell movement (5,6).…”
mentioning
confidence: 99%
“…Instead, we assume that depolymerization takes place everywhere in the bulk of the cell as it is suggested by observations [66][67][68][69].…”
Section: B Delocalized Depolymerizationmentioning
confidence: 99%
“…We therefore assume a smaller value v + 1 which is also plausible in view of [28,31,67,68]. In the presence of elasticity penalizing infinite stretching such re-scaling is not necessary.…”
Section: B Delocalized Depolymerizationmentioning
confidence: 99%